CRISPR-Cas9: a powerful tool to efficiently engineer Saccharomyces cerevisiae - Costa, João Manuel Rainha (2021)
Saccharomyces cerevisiae has been for a long time a common model for fundamental biological studies and a popular biotechnological engineering platform to produce chemicals, fuels, and pharmaceuticals due to its peculiar characteristics. Both lines of research require an effective editing of the native genetic elements or the inclusion of heterologous pathways into the yeast genome. Although S. cerevisiae is a well-known host with several molecular biology tools available, a more precise tool is still needed. The clustered, regularly interspaced, short palindromic repeats–associated Cas9 (CRISPR-Cas9) system is a current, widespread genome editing tool. The implementation of a reprogrammable, precise, and specific method, such as CRISPR-Cas9, to edit the S. cerevisiae genome has revolutionized laboratory practices. Herein, we describe and discuss some applications of the CRISPR-Cas9 system in S. cerevisiae from simple gene knockouts to more complex processes such as artificial heterologous pathway integration, transcriptional regulation, or tolerance engineering.